(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Cesium iodide crystal activated with thallium (CsI(Tl)) is used as radiation sensor because of its favorable characteristics as scintillator, when excited by gamma radiation. This crystal has good mechanical strength and it is relatively little hygroscopic. In the present work, the CsI(Tl) crystal was grown in the Nuclear Energy Research Institute (IPEN/CNEN/SP) by Brigdman technique, in two different formats: (a) cylindric (∅ 20.1 mm x 11.9 mm) and (b) parallelepiped ( c 12.3 mm x 19.5 mm). The scintillator response was studied through five gamma radiation sources: 99mTc (140 keV), 137Cs (662 keV), 60Co (1173 keV, 1333 keV) and 22Na (511 keV, 1275keV). The crystals were coupled to a photomultiplier tube using 0.5 McStokes viscosity silicone grease as the optical interface. All electronics for signal measurements were developed at IPEN. Luminescence property of the CsI(Tl) crystal was excited by the radiation from a 99mTc source. The energy resolution of the crystalline detector was determined by the FWHM parameter, corresponding to the photopeak width at half of its height. Gamma radiation was spectrometry performed with the following sources: 99mTc, 241Ba, 137Cs, 60Co and 22Na.